2020
DOI: 10.1038/s41598-020-61518-w
|View full text |Cite
|
Sign up to set email alerts
|

In vivo engineering of lymphocytes after systemic exosome-associated AAV delivery

Abstract: Ex-vivo gene therapy using stem cells or t cells transduced by retroviral or lentiviral vectors has shown remarkable efficacy in the treatment of immunodeficiencies and cancer. However, the process is expensive, technically challenging, and not readily scalable to large patient populations, particularly in underdeveloped parts of the world. Direct in vivo gene therapy would avoid these issues, and such approaches with adeno-associated virus (AAV) vectors have been shown to be safe and efficacious in clinical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…In an AV vector system, association of VV to vesicles improved the efficacy of oncolytic virus therapy on tumors with low coxsackie-and-adenovirus (CAR) [ 34 ]. In AAV exosome, associated AAV8 vectors were demonstrated to efficiently transduce lymphocytes after systemic delivery [ 39 ].…”
Section: Discussion—impact Of Ev-vi Interplay On Viral Vector Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…In an AV vector system, association of VV to vesicles improved the efficacy of oncolytic virus therapy on tumors with low coxsackie-and-adenovirus (CAR) [ 34 ]. In AAV exosome, associated AAV8 vectors were demonstrated to efficiently transduce lymphocytes after systemic delivery [ 39 ].…”
Section: Discussion—impact Of Ev-vi Interplay On Viral Vector Technologymentioning
confidence: 99%
“…Similar to the situation for AV, knowledge on the influence of EVs on wt AAV infections is scarce. Indeed, information on wt parvovirus relationships to EVs is mostly found in the context of research on vector systems [ 39 , 40 ]. For other groups of non-enveloped viruses, such as members of the families Picornaviridae , Reoviridae and Papillomaviridae , interactions with EV are well documented.…”
Section: Virus-vesicle-interplay: Anti- and Proviral Modalitiesmentioning
confidence: 99%
“…As an innovative approach, AAV-associated exosomes have been reported to efficiently deliver genes to the central nervous system (Hudry et al, 2016;Volak et al, 2018), immune cells (Breuer et al, 2020), retina (Wassmer et al, 2017), cochlea (György et al, 2017), and liver cells (Meliani et al, 2017). Our study has shown great potential that AAVExo may enhance the existing gene therapies for cancer treatment.…”
Section: Discussionmentioning
confidence: 68%
“…Only recently, in vivo transduction of mouse lymphocytes with serotype-8-derived vectors was described. 43 Our data suggest that efficient binding to T cells via CD8 enables efficient gene delivery with AAV2 vectors. This stresses the crucial role of high-affinity targeting ligands displayed on the particle surface.…”
Section: Discussionmentioning
confidence: 71%